2005
DOI: 10.1117/12.622252
|View full text |Cite
|
Sign up to set email alerts
|

Overview of NRL's maritime laser communication test facility

Abstract: NRL has established a 20 mile round trip laser communication test facility across the Chesapeake Bay for investigating lasercomm performance in a maritime environment. Experiments at this facility have successfully demonstrated links at data rates up to 2.5 Gbps and at lower rates in light rain and fog. This facility is currently being upgraded to allow long term monitoring of a one-way 10 mile link across the Bay. Parameters monitored will include BER, turbulence conditions, atmospheric transmission, and mete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Several experimental data and measurements indicate that the turbulence in the upper troposphere and stratosphere, or along nonhomogeneous path, deviates from predictions of the Kolmogorov model [2][3][4][5][6]. Other experiments showed that atmospheric turbulence in maritime environments can assume a different statistical behavior with respect to Kolmogorov [7][8][9][10][11][12][13]. In addition, anisotropy in stratospheric turbulent inhomogeneities has been experimentally investigated [14][15][16][17], and laboratory results have shown that turbulence can be anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental data and measurements indicate that the turbulence in the upper troposphere and stratosphere, or along nonhomogeneous path, deviates from predictions of the Kolmogorov model [2][3][4][5][6]. Other experiments showed that atmospheric turbulence in maritime environments can assume a different statistical behavior with respect to Kolmogorov [7][8][9][10][11][12][13]. In addition, anisotropy in stratospheric turbulent inhomogeneities has been experimentally investigated [14][15][16][17], and laboratory results have shown that turbulence can be anisotropic.…”
Section: Introductionmentioning
confidence: 99%
“…Both locations are in Maryland and are separated by 16.2 km of water. Significant improvements have been made this past year in the facilities' resources which are described elsewhere in this Proceedings (13). Most notably are the new capabilities to enable long term monitoring of atmospheric conditions.…”
Section: Testbedsmentioning
confidence: 99%
“…Previously, results have been reported on our round trip propagation results, where an array of 25 solid retroreflectors located on a tower on NRL-Tilghman Island, MD folded the optical link back to the CBD facility on the western side of the Chesapeake Bay [15][16][17][18][19][20] . The conversion to a one-way propagation path allows for a more accurate characterization of the path because the angle-of-arrival and C n 2 measurements are made along one direction.…”
Section: Lasercom Test Facilitymentioning
confidence: 99%
“…These thermal gradients change on a time scale of several minutes to hours, depending on the weather conditions. [14][15][16][17] The output of the communication receiver (APD #3) is used for BER testing, packet error rate (PER) testing or video transmission. Details of the test setups and comparisons of BER and PER testing have been presented previously in reference 20.…”
Section: Lasercom Test Facilitymentioning
confidence: 99%